Effects of some phosphorus sources and liming on peanut seed quality - Nakagawa, João; Nakagawa, Júlio; Imaizumi, Issao; Rosseto, Cláudia A.V. (Pesquisa Agropecuaria Brasileira, 2014)
The effects of some phosphatic fertilizers, with and without limestone on peanut (Arachis hypogaea L.) seed quality were studied. The phosphorus sources employed were: simple superphosphate, hyperphosphate, yookarin, thermophosphate (yoorin) and partly acidulated phosphate. The limestone was applied to increase the base saturation of soil until 70%; the doses of N-P205 -K 2O used were 20, 100 and 30 kg/ha. Experiments were carried out under field conditions in two localities, Julio Mesquita and Manilia, both located in the state of São Paulo, Brazil. Fertilizers and limestone were applied in the wet season crop and their residual effects also observed in the dry season crop. The cultivar sowed was Tatu Branco. In Julio Mesquita, the limestone presence yielded seeds with higher germination and vigor than in absence, in both crop seasons. In Manila, the positive effect of liming on seed quality was more evident in the wet season crop than in the dry season crop. The effects of all phosphatic fertilizers on physiological quality of seed were similar in Julio Mesquita, but they presented some differences in Manilha, in both season crops.